The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/cb.1692
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and outcomes of price premium and loyalty: A food case study

Abstract: This paper examines determinants and outcomes of price premium and loyalty on a food product.The study attempts to fill this gap by offering new insights into consumer's perspectives, as concerns food marketing, and to empirically test a model that includes five determinants or drivers: awareness, corporate social responsibility, origin, quality, and positioning. Furthermore, the greater or weaker impact of price premium and loyalty on their outcomes have been also studied, specifically, the influence that wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 67 publications
(224 reference statements)
2
14
1
5
Order By: Relevance
“…Over the last four decades, research on customer loyalty factors has been a prolific field. Marketing scholars [9,11,[13][14][15][16][18][19][20] have developed and validated more than one hundred different factors determining customer loyalty. Classifications of factors determining customer loyalty show that researchers' opinions on collections of factors vary.…”
Section: Factors Determining Customer Loyaltymentioning
confidence: 99%
See 3 more Smart Citations
“…Over the last four decades, research on customer loyalty factors has been a prolific field. Marketing scholars [9,11,[13][14][15][16][18][19][20] have developed and validated more than one hundred different factors determining customer loyalty. Classifications of factors determining customer loyalty show that researchers' opinions on collections of factors vary.…”
Section: Factors Determining Customer Loyaltymentioning
confidence: 99%
“…Price is viewed as an important factor, especially for middle-income earners and/or in commodity-based sectors [13,47]. Customers tend to compare the price of the service provider of a particular type of service with prices of other providers offering the same service.…”
Section: Service Provider Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has indicated that in business markets, a brand can create price premium [73,75,76], especially when the brand has high brand awareness, perceived quality, and perceived prestige value. Thus, even though there is a price increase, consumer's responses towards the brand will stay the same or more elastic.…”
Section: Price Premium (Pp)mentioning
confidence: 99%